2020
DOI: 10.1002/met.1950
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drought impacts on crop yields across Nepal during 1987–2017

Abstract: Drought influences agriculture, hydrology, ecology and socioeconomic systems globally. As agriculture is the primary source for livelihoods and contributes to $27% of Nepalʼs total gross domestic product, it is essential to understand the impact of drought on maize and wheat crop yields to minimize the droughtrelated risks. This study presents insights about agricultural drought across Nepal during 1987-2017 using the Standardized Precipitation Evapotranspiration Index (SPEI). The temporal evolution of SPEI ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 74 publications
3
46
0
Order By: Relevance
“…No continuous drought has been observed (Kafle, 2015) On average, the intensity of drought is high in higher mountains (Baidya et al, 2008;Shrestha, 2000) as low precipitation is observed in western high-mountain areas (Kansakar et al, 2004). Also, the occurrence of winter drought has increased from 2015 onwards (Hamal et al, 2020) as predicted (Baniya et al,2019).…”
Section: Seasonal Drought Frequencymentioning
confidence: 92%
See 4 more Smart Citations
“…No continuous drought has been observed (Kafle, 2015) On average, the intensity of drought is high in higher mountains (Baidya et al, 2008;Shrestha, 2000) as low precipitation is observed in western high-mountain areas (Kansakar et al, 2004). Also, the occurrence of winter drought has increased from 2015 onwards (Hamal et al, 2020) as predicted (Baniya et al,2019).…”
Section: Seasonal Drought Frequencymentioning
confidence: 92%
“…Among all the provinces, Karnali ranks first in the production of barley (GoN/MoF, 2019). Karnali Province faces a higher probability of drought spells that can last from few months of a season to droughts lasting a year (Hamal et al, 2020). Furthermore, the study area ( Fig.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations